2017
DOI: 10.1097/md.0000000000007880
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of tranexamic acid in reducing blood loss in total shoulder arthroplasty

Abstract: Background:The purpose of this meta-analysis is to compare the efficacy of tranexamic acid (TXA) versus placebo after a total shoulder arthroplasty (TSA).Methods:In April 2017, a systematic computer-based search was conducted in the databases of PubMed, Embase, Web of Science, Cochrane Library, and Google. Studies comparing TXA versus placebo in reducing blood loss after TSA were included. The endpoints were the need for transfusion, blood loss in drainage, hemoglobin drop, and total blood loss. Stata 12.0 sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…No adverse events were recorded, which is consistent with the recently published meta-analyses of TXA use in shoulder arthroplasty that found no adverse events across all studies. 4,21,28,43,49 This finding is also consistent with results from hip and knee arthroplasty. 14,16,25,36,50 TXA use in shoulder arthroplasty has received significant recent interest.…”
Section: Discussionsupporting
confidence: 88%
“…No adverse events were recorded, which is consistent with the recently published meta-analyses of TXA use in shoulder arthroplasty that found no adverse events across all studies. 4,21,28,43,49 This finding is also consistent with results from hip and knee arthroplasty. 14,16,25,36,50 TXA use in shoulder arthroplasty has received significant recent interest.…”
Section: Discussionsupporting
confidence: 88%
“…Three meta-analyses 14,16,18 reported significant reduction of blood transfusions after SA with TXA, whereas other three 13,15,17 did not find significant differences on transfusions after SA between TXA and placebo (Table 4). Possible reasons for these contradictory results include the inclusion of retrospective non-randomized studies, the use of different pooling methodologies to produce a combined estimate (i.e.…”
Section: Relation To Other Meta-analysesmentioning
confidence: 98%
“…The question of whether TXA is effective in decreasing blood loss in SA is already resolved. [13][14][15][16][17][18] However, whether TXA remains as a cost-effective intervention even if it has no or minimal effect on transfusion rates, the best dose and route of administration of TXA in SA and the effect of TXA on subpopulations of SA patients with differential risks are still unanswered questions. There is a need for large multicenter pragmatic RCTs to examine the effectiveness of TXA on clinically relevant outcomes in a heterogeneous group of patients undergoing SA, including patients with a higher baseline risk of transfusion (e.g.…”
Section: Unanswered Questions and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent systematic reviews have demonstrated TXA to be effective in reducing blood loss and transfusion rates in lower limb arthroplasty and spinal surgery [10] , [11] , [12] . Most recently, clinical trials investigating its use in shoulder arthroplasty have shown favourable results [13] , [14] , [15] , [16] , [17] , [18] . The overall clinical effectiveness of tranexamic acid use in shoulder surgery is of interest.…”
Section: Introductionmentioning
confidence: 99%